Pengaruh Saluran Distribusi dan Kualitas Produk Terhadap Volume Penjualan (Studi Kasus pada Kelompok Tani Jagung di Sampang) - Rahmawati, Novia; Syarif, Muh (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
This research aims to determine the influence of distribution channels and product quality on the sales volume of corn agricultural products in Sampang. The sample from this research was 25 groups of corn farmers in Sampang aged over 17 years and over and managing corn farming businesses. The data collection technique in this research uses a questionnaire with a Likert scale. The data analysis technique uses multiple regression analysis. The t test is used to test the significance of variations in the relationship between variables X and Y, whether variable X has a partial effect on variable Y (sales volume). Meanwhile, the F test is to determine the simultaneous effect. In this research, SPSS software program tools were used to simplify the research data processing process. Reliability and validity tests were carried out to test the questionnaire. This research proves the influence of distribution channels and product quality on sales volume among farmer groups in Sampang. Distribution channels bring products quickly to consumers so they can be sold and product quality that attracts consumers' attention to increase sales volume.